A Conceptual Framework Describing Mercury Bioavailability to Microbes Through Redox Zones - Stenzler, Benjamin (Université d'Ottawa / University of Ottawa, 2022)
Mercury (Hg) is a global pollutant and potent neurotoxin that is detrimental to the environment and human health. (MeHg). All forms of Hg are toxic, but methylmercury (MeHg) can biomagnify through food webs and become concentrated in food staples such as fish and rice, creating an exposure risk to people. The conversion of Hg to MeHg is mediated by anaerobic microbes, particularly sulfate and iron-reducing bacteria and methanogenic archaea. However, Hg methylation is an intracellular process, and MeHg production is dependent on the bioavailability of inorganic Hg to these microbes. One outstanding knowledge gap in understanding Hg methylation is the nature of bioavailability of inorganic divalent Hg (HgII). Much research has gone into developing a framework describing how microbes take up Hg for methylation. Still, the framework describing Hg bioavailability processes is not fully developed. The overall objective of my thesis is to address these mechanisms governing HgII bioavailability to anaerobic microbes. HgII bioavailability is determined by its speciation; these are all the different forms and compounds of HgII. To address the bioavailability of various HgII species, I used microbial Hg-biosensors. Hg-biosensors are bacterial cells that emit a quantifiable signal when HgII enters them and let me observe HgII bioavailability in real-time. The biosensors I developed are the first Hg-biosensors that function without oxygen and let me explore HgII species and their bioavailability under conditions conducive to methylation. HgII speciation is spatially and temporally dynamic moving from oxic to anoxic conditions and under various biogeochemical controls. I follow HgII speciation and bioavailability in my thesis as it transgresses through these conditions. Understanding HgII bioavailability to complex microbial communities across redox gradients and through dynamic ligand interactions is a missing key component to understanding and predicting MeHg formation. My results show how altering HgII speciation can identify novel bioavailability pathways or make it completely inaccessible. My results highlight how microbes can control HgII bioavailability and the importance of microbial community structure on metal acquisition. First, I resolve pathways for charged inorganic HgII species through the cell membrane and demonstrate novel pathways for previously unconsidered charged species. Using dissolved organic matter (DOM) originating from various algal species, I show how algae can uniquely control HgII bioavailability to other organisms. I demonstrate how DOM has emergent properties that can control HgII bioavailability. Next, I investigated the compounds microbes use to scavenge metals such as iron and copper. I reveal how they could inadvertently interact with HgII and form new bioavailability pathways. Lastly, I demonstrate how the diffusion of biogenic hydrogen sulfide from an isolated system can make an otherwise non-bioavailable HgII species rapidly available for microbial uptake. Overall, my thesis expands the framework describing HgII bioavailability to microbes and potential drivers of Hg methylation in the environment.
Keywords: Mercury; Biosensor; Anaerobic; Bioavailability